ALTERNATIVE BODILY PRACTICE AND YOGA: RELATIONS BETWEEN MEDIA AND CONSUMPTION (Fiep Bulletin - online, 2014)
Yoga practice has become very popular in the last decades. The academy spaces offer different types of yoga practices at the same time and space as aesthetical and modeling practices are available. Frequent inclusion of yoga in publicity, associating it with different products in the alternative universe indicates the assimilation of the eastern influence and of this practice. This study aims at identifying how yoga is represented in the printed media in the form of publicity pieces. Magazines and newspapers between 2006 and 2007 were used. The hypothesis is that yoga previously considered a strange practice in our culture has not only been accepted, but has also become the object of desire as a consumption good. This is a qualitative, descriptive and exploratory survey. The sample was made up by eight publicity pieces of everyday products. The theoretical reference is based on Barthe (1971) and on Campbell (2001). The interpretation of the data was made according to the imagistic analysis by Joly (2001), considering the plastic, iconic and linguistic message and the contents analysis (BARDIN, 1977). One can identify the prevalence of the lotus position and the classical yoga balance, female and male figures with harmonious, flexible and active forms as an iconic element and the linguistic message highlighting the words: balance, lightness, freshness, tranquility, health, vitality, confidence, security and awareness. It was concluded that the elements associated with yoga represent values desired by consumers and offered by yoga.
Keywords: social representation; yoga; media; consumption